PERTANGGUNGJAWABAN PIDANA KORPORASI ATAS PRAKTIK TRANSFER PRICING BIDANG PERPAJAKAN DI INDONESIA - Antonius Leonard Tarigan; Bismar Nasution; Mahmul Siregar; Mahmud Mulyadi (Universitas Sumatera Utara, 2017)
ABSTRACT The research shows that the corporate crime liability in Indonesia can be liable to the member of board of directors in a corporate if they commit in deliberate and negligent way. A corporate is also a crime subject other than human being. Therefore, a corporate can be convicted crime based on functional liability (functioneel daderschap). In transfer pricing case, if it was committed deliberately to avoid or minimized tax payment to the country which impact to loss for the country. The corporate crime libility of transfer pricing practice in Indonesia’s taxation is a deliberate action by a corporate as the effort of tax avoidance which reduce the tax contribution to the country. The deliberate action includes motivation and intention to avoid tax which impact to losses for the country. Transfer pricing is basically an intentional effort in a corporation to avoid tax payment. In other words, a corporation may be crimely liable if there is an intentional effort to avoid tax which impact to losses for the country, violating its obligation as the tax payer. The model of corporate crime liability of transfer pricing in taxation based on tax regulation for corporate is being charged with tax evasion, while for directors of officers may be crimely convicted of deliberate act to avoid paying tax by manipulating transfer price. Keyword: crime liability, corporation, taxation, transfer pricing